2008
DOI: 10.1016/j.tetlet.2008.07.169
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic asymmetric addition of alkyl- and aryl-zinc reagents to an isoxazole aldehyde

Abstract: Nucleophilic addition of alkyl-and aryl zinc reagents to a C(4) functionalized isoxazolyl aldehyde proceeded effectively with high enantioselectivity (85-94% e.e.). The amino alcohol catalyst (S)-2-piperidinyl-1,1,2-triphenyl ethanol (10) afforded the (R)-product 2b, as established by x-ray crystallography.Functionalized isoxazoles represent an extremely important class of compounds in the synthesis of therapeutically relevant molecules. 1 The recent report of Myers on the asymmetric addition of zinc reagents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The amino acid analogues of AMPA were prepared using synthetic methodology previously described by our laboratory, with the exception of MOM- and BOM-ACPA, 7b and 7e respectively, which were prepared from the known 5-hydroxymethylene acetal 18, via a straightforward Williamson ether synthesis, and carried forward to the amino acids using our previously described sequence 19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid analogues of AMPA were prepared using synthetic methodology previously described by our laboratory, with the exception of MOM- and BOM-ACPA, 7b and 7e respectively, which were prepared from the known 5-hydroxymethylene acetal 18, via a straightforward Williamson ether synthesis, and carried forward to the amino acids using our previously described sequence 19.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids, racemic ACPA ((±)- 7 ) 45, (±)- 8 (S)-ACPA, ((−)-7) , 7d, 7g, 7f 19, 7a and (S,S)- 7c 18 were prepared using methods previously described by our laboratories, and full experimental details have been published. (S)-MOM-ACPA ( 7b ) and BOM-ACPA ( 7e ) 46 were prepared from 12 via the known 5-hydroxyl-methyl acetal 18 using the amino acid synthesis sequence previously described 19.…”
Section: Methodsmentioning
confidence: 99%
“…Spectroscopic data were identical with those of racemic 3a. 12 HPLC separation on a chiral stationary phase (Chiracel AS column, 254 nm detector, 1 ml/min, 30:1 hexanes: EtOH) showed that the product had a 43% enantiomeric excess. 3-methyl-isoxazol-4-yl]-1,4-dihydropyridine-3,5-dicarboxylate 3i.…”
Section: Synthesis Of Ethyl 5-[1-hydroxyethyl]-4-(255-trimethyl-13mentioning
confidence: 99%
“…11,12 Over fifty attempts employing chiral bis-oxazolines, 13 Shibasaki's lanthanum BINOL, 14 Jacobsen's salen aluminum catalyst, 15 and Sparteine, 16 in the lateral metalation reaction failed to produce a significant enantio-enrichment of the product. We sought an alternate route which would provide synthetically useful results, and now report that the use of the Corey-Bakshi-Shibata (CBS) 17 reduction on isoxazolyl ketones produces chiral isoxazolyl carbinols in uniformly excellent chemical yields with high enantiocontrol in many cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation